2012
DOI: 10.1097/pas.0b013e3182653ece
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Markers on Needle Biopsies Are Helpful for the Diagnosis of Focal Nodular Hyperplasia and Hepatocellular Adenoma Subtypes

Abstract: Phenotypic identification of focal nodular hyperplasia (FNH) and hepatocellular adenoma (HCA) subtypes using immunohistochemical markers has been developed from their molecular characteristics. Our objective was to evaluate the sensitivity of these markers in the definitive diagnosis of these lesions by core needle biopsies. A total of 239 needle biopsies paired with their surgical resection specimen (group A) or without an associated resection specimen (group B) were reviewed. Using a step-by-step algorithm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 30 publications
5
94
1
2
Order By: Relevance
“…24 In view of these morphological challenges, immunohistochemical staining for glutamine synthetase and serum amyloid-associated protein is increasingly being used to confirm the diagnosis. 14 Our results highlight the utility and the pitfalls in interpretation of these stains (Table 5). Glutamine synthetase shows pericentral staining in the normal liver and map-like glutamine synthetase staining in virtually all the cases of focal nodular hyperplasia.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…24 In view of these morphological challenges, immunohistochemical staining for glutamine synthetase and serum amyloid-associated protein is increasingly being used to confirm the diagnosis. 14 Our results highlight the utility and the pitfalls in interpretation of these stains (Table 5). Glutamine synthetase shows pericentral staining in the normal liver and map-like glutamine synthetase staining in virtually all the cases of focal nodular hyperplasia.…”
Section: Discussionmentioning
confidence: 56%
“…12,13 In focal nodular hyperplasia, there is expansion of the b-catenin-activated centrizonal region, which leads to overexpression in a characteristic geographic map-like pattern. [14][15][16] Diffuse cytoplasmic expression of glutamine synthetase is seen in a small subset of b-cateninactivated hepatocellular adenomas, but the map-like pattern typical of focal nodular hyperplasia is not observed in hepatocellular adenomas. On the other hand, inflammatory hepatocellular adenomas, but not focal nodular hyperplasia, show cytoplasmic staining with antibodies to acute phase reactants, including serum amyloid-associated protein and C-reactive protein.…”
mentioning
confidence: 99%
“…While immunohistochemical staining of LFABP, β-catenin, glutamine synthetase, serum amyloid A, and C-reactive protein has proven to be very effective in differentiating between the four subtypes of HCA, it is also useful in the differentiation between HCA and FNH (9,20). In a retrospective, multicenter study in France, Bioulac-Sage et al (20) found that the certainty of biopsy diagnosis of FNH increased from 53% to 87% when additional immunohistochemistry markers and glutamine synthetase immunostaining were used.…”
Section: Implications For Diagnosismentioning
confidence: 99%
“…Currently, liver ultrasound (US) and MRI are the recommended diagnostic imaging tools for characterizing the lesion and subsequent follow-up. Glutamine synthetase is a nitrogen metabolism enzyme with a distribution in the human liver characterized by its strict pericentrolobular localization [25] . It has emerged as a good marker for identification of resected FNH and for differentiating FNH from all other types of hepatocellular nodules developed on normal liver [26] .…”
Section: Focal Nodular Hyperplasiamentioning
confidence: 99%